Oral ulcerative lesions: a review of 55 cases in Benin-City, Nigeria - O.F. Omoregie; M. Okoh (Nigerian Dental Association, 2014)
Objective: This study aims to determine the incidence, age, gender, site and treatment outcome of oral ulcerative lesions in Benin City, Nigeria. Method: This is a 3-year retrospective review of all ulcerative oral lesions seen at the Dental Centre, University of Benin Teaching Hospital, Benin City, Nigeria. The medical records, laboratory and histopathology reports of the patients seen between April 2008 and March 2011 the study period were reviewed. All cases of oral ulcerations were selected and patients with erosive mucosa lesions were excluded from this study. Result: A total of 55 (1.3%) cases of oral ulcers were diagnosed amongst the 4092 oral lesions seen within the study period. There were 33(60.0%) males and 22 (40.0%) females, giving a ratio of 1.5:1. Most of the patients were in the 3rd decade (n=18, 32.7%). Recurrent aphthous ulcer (n=26, 47.3%) was the most frequent lesion, followed by infective ulcers (n=9, 16.4%), traumatic ulcers (n=8, 14.5%), immune mediated ulcers (n=7, 12.7%) and neoplastic (malignant) ulcers (n=5, 9.1%). Majority of the ulcers occurred in multiple oral mucosal sites (n=21, 38.1%), while the gingiva (n=10, 18.2%) was the commonest solitary oral mucosal site for the ulcers. A good treatment outcome was observed for most of the oral ulcers except for the deep mycosis and malignant oral ulcers. Conclusion: A lower incidence of oral ulcers was observed in this study compared to previous report in a black African population. The oral ulcers were commoner in adult males and the gingiva was the most frequent solitary site. The lesions were mostly those of local origin, with RAU accounting for majority of the cases studied. The treatment outcome was good for most of the oral ulcers except for the deep mycosis and malignant oral ulcers.